Farmers' perceptions of the challenges facing the biomass market in Poland; a case study from South and Central Poland. Issue 7 (2nd July 2021) - Zyadin, Anas; Natarajan, Karthikeyan; Igliński, Bartłomiej; Iglińska, Anna; Kaczmarek, Aleksandra; Kajdanek, Jakub; Trishkin, Maxim; Lisowski, Aleksander; Dąbrowska, Magdalena; Pelkonen, Paavo; Pappinen, Ari
Abstract: Farmers' perceptions and values are a fundamental part of a polycentric approach aimed at improving the financial feasibility of biomass-based enterprises. In this survey-based study, 210 farmers from central (Toruń province) and southern (Upper Silesia region) Poland completed a self-instructed questionnaire dealing with their perceptions of the challenges currently facing the biomass market and their willingness to change from traditional farming to feedstock production for energy generation. The results indicate that only 12% of the farmers are willing to switch to biocrop cultivation. Moreover, selected socio-economic and demographic variables (gender, age) had an impact on their willingness to adopt energy crops. All the presented challenges appeared to be of high relevance to the farmers who participated in this study. However, farmers from Toruń province attributed substantial relevance to the social transformation in the agriculture sector, and to the lack of seasonal workers. In the Upper Silesia region, the lack of a well-established biomass market was of greatest relevance. A cross-tabulation method revealed statistical differences between the perceived value of farming and the farmers' perceptions toward the challenges facing the biomass market. These findings are insightful for policies that aim to address the shortcomings in current biomass market development in Poland.